2020
DOI: 10.3390/biomedicines8010012
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of NMES and Mendelsohn Maneuver on the Swallowing Function and Swallowing–Quality of Life of Patients with Stroke-Induced Sub-Acute Swallowing Disorders

Abstract: It is necessary to identify how to improve the swallowing-related quality of life, as well as the swallowing function, in order to evaluate the effect of treatments on swallowing disorders. This study aimed to prove the effects of a compound swallowing intervention (Mendelsohn maneuver + neuromuscular electrical stimulation (NMES)) on the swallowing function and the quality of life by applying the compound swallowing intervention to patients with sub-acute swallowing disorders due to cerebral infarction for ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
0
26
0
4
Order By: Relevance
“…A total of 21 articles were found, of which eleven were focused on experimental researchs [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and nine were randomized-controlled trials [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The methodological characteristics of the analysed studies are shown in Table 2 and, in Table 3 , the characteristics of the interventions applied in them are presented.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 21 articles were found, of which eleven were focused on experimental researchs [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and nine were randomized-controlled trials [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The methodological characteristics of the analysed studies are shown in Table 2 and, in Table 3 , the characteristics of the interventions applied in them are presented.…”
Section: Resultsmentioning
confidence: 99%
“…The application of NMES was not conducted using the same parameters in the analysed investigations. Regarding the application frequency, the choice of 80 Hz was the most widely used [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 45 ], although, in several cases, this parameter was not mentioned [ 34 , 38 , 44 , 46 ] and in another two studies the authors selected lower frequencies (60 [ 47 ] and 30 Hz [ 43 ]). In all cases, the results were statistically significant; even those studies which used lower frequencies obtained significant reductions in oral and pharyngeal transit time [ 47 ], significant decreases in the severity of penetration and aspiration [ 43 ] and significant increases in the level of oral intake and quality of life [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations